BINA MANUSIA DAN BINA USAHADI DESA WANUREJO KABUPATEN MAGELANG - Darmawan, Ridho Bagus (Jurnal Pallangga Praja (JPP), 2022)
This research aims to describe the form of Human development and Business development through BUMdes eka Nawa Karsa wanurejo Village, Borobudur district, Magelang Regency. BUMdes eka Nawa Karsa has three (3) types of businesses established in 2016 to help the economy of the community in wanurejo Village. This research is descriptive research and uses qualitative approach, namely by way of researchers jumping directly into the field to conduct observations, interviews and documentation. The focus of this research is community empowerment using two (2) indicators, namely with Human development and Business development. data analysis techniques are data collection, data reduction, data presentation, and conclusion drawing. The results showed that Bina Manusia and Bina Usaha have not been running well. Through the indicators of Human development through BUMdes eka Nawa Karsa has been running well but has not gone well such as training and seminars that are lacking and the selection of recruitment of workers is less to the perpetrators and the community assisted by BUMdes eka Nawa Karsa. Meanwhile, if seen from Bina Usaha for bumdes capital in the form of funds and infrastructure facilities are still lacking so it is still constrained while the certification of BUMdes assisted Community products has not been facilitated by BUMdes and the village government. so that researchers provide advice to add training and seminars to bumdes management and community and capital assistance to bumdes management and community should be distributed regularly.